PENGARUH BIAYA AGENSI, KESEMPATAN INVESTASI, HUTANG, LIKUIDITAS, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP DIVIDEND PAYOUT RATIO - Purweni Widhianningrum (Assets: Jurnal Akuntansi dan Pendidikan, 2013)
The purpose of this research is to to determine the effect of agency costs (which is proxied by managerial ownership and institutional ownership), investment opportunities (which is proxied by firm age, market to book value and growth), debt, liquidity, profitability, and firm size on dividend payout ratio. The reseach is used manufacturing companies listed in IDX for periode 2003 until 2007 for object research, with total of population 151 companies.  The method of data collection is done by using polling data method and give 205 total  observation. Analysis method that use in this research is multiple regression analysis. The result of this reseach show that managerial ownership, institusional ownership, age of the firms, market to book value,  growth, debt to equity ratio, current ratio, return on asset and size of the firms simultanous have positive influences to devidend payout ratio. For partial influences, managerial ownership, age of the firms, debt to equity ratio, current ratio, return on asset and size of the firms have positive influences, and institusional ownership, market to book value,  growth have negative influences to dividend payout ratio. Debt to equity ratio have a dominant influences to dividend payout ratio.